Junk Food Consumption Among Secondary Level Students, Chitwan - Sapkota, Shubha Devi; Neupane, Seema (Journal of Nepal Paediatric Society, 2018)
Introduction: Junk food is a pejorative term for cheap food containing high levels of calories from sugar or fat with little fibre, protein, vitamins or minerals. This study was conducted to assess the junk food consumption and patterns of consumed junk food among secondary level students. Material and Methods: This was a descriptive cross-sectional research. Hundred forty-two respondents were drawn by using cluster sampling method. Self-administered semi-structured questionnaire in Nepali Version was used and the collected data was entered and analysed in Epi-data and SPSS Version 20 by using simple statistical methods. Results: The findings revealed that more girls (53.5%) consumed junk food than boys (79.6%) and those respondents were aware of the meaning of junk food. Majority of respondents (90.1%) preferred junk food for taste, is faster to prepare (44.4%), preferred as influenced by TV advertisements (15.5%), because of peer influences (31.7%) and some (29.6%) respondents preferred junk food because nothing else was available. Concerning patterns of consumed junk food all respondents (100%) consumed ‘chat-pat’ and noodles, panipuri (97.2%), doughnuts (93%), chocolates (92.3%), biscuits (95.8%), ice cream (65.5%) and cold drinks (65.5%). Only 54.2% of respondents were aware of risks associated with poor eating habits. Conclusion: Adolescents consumed a greater amount of junk food which led to a majority of ill effects later on. It is recommended that the school and community conduct and implement awareness programme on junk food consumption and its ill effects.